Effectiveness of breathing exercises, foot reflexology and massage on maternal and new-born outcomes among prim gravidae in Saudi Arabia - Kamilya, Baljon (2021)
Introduction: Labour pain is an individual experience and one of the most severe pain that primigravidae may experience. Failure of a pregnant woman to address labour pain and anxiety may lead to abnormal labour. Despite the availability of many complementary non-pharmacological approaches, the quality of evidence is low, and the best approaches have yet to be established. Therefore, this study was aim to investigate the effects of a combination of breathing exercises, foot reflexology and back massage (BRM) on the labour experiences of primigravidae. This randomized controlled trial involved an intervention group receiving BRM and a control group receiving standard labour care. The two groups are stratified by intramuscular pethidine in labour to ensure each subgroup of the population is received suitable representation within the sample. This achieves a balance in the number of primigravidae with or without intramuscular pethidine given to intervention and control groups. Primigravidae at 24th week to 34th week of gestation without chronic diseases or pregnancy-related complications were recruited from antenatal clinics. The BRM intervention: Breathing exercises five minutes, foot reflexology 20 minutes, and leg and back massage 35 minutes was performed by a trained massage therapist who trained the research coordinators, the outcomes assessors, and the massage therapists. The primary outcomes included labour pain and anxiety. The labour pain was measured during and after uterine contractions at baseline (cervical dilation 6cm), during the intervention, immediately after the intervention, and every 60 minutes for two hours, while anxiety was measured at baseline (cervical dilation 6cm), immediately after the intervention, and every 60 minutes for two hours. The secondary outcomes that observed maternal outcomes included maternal stress hormone (adrenocorticotropic hormone, cortisol, and oxytocin) levels, vital signs, duration of the labour, maternal satisfaction, and new-born outcomes including foetal heart rate and APGAR scores. Methods: The between- and within-group outcome measures were examined with the generalized linear mixed model, time series analyses, post hock test and Bonferroni test; non-parametric tests to compare between the groups.The sample size is estimated based on the between-group difference of 0.6 in anxiety scores, which were lower different effect sizes, thus, it will produce a larger sample size estimation that can be used to measure both different pain and anxiety, 95% power and 5% α error, which yields a required sample size of 184 primigravidae (92 in each group) accounting for a 40% attrition rate. Ethical approval was obtained from the Ethical Committee for Research Involving Human Subjects of the Ministry of Health in Saudi Arabia (H-02-K-076-0319-109) on 14 April 2019 and from the Ethics Committee for Research Involving Human Subjects (JKEUPM) Universiti Putra Malaysia on 23 October 2019, reference number (JKEUPM-2019–169). Results: A total of 253 participants were eligible for the study; however, 225 of them (response rate of 88.9%) agreed to participate in the study. They were randomized into the intervention group (n=113), and the control group (n=112). Throughout the study, 19 participants from the intervention group and 22 participants from the control group dropped out of the study. Depending on the dropped out participants from the trial, that resulted in 94 participants in the intervention group and 90 in the control group. Baseline characteristics between the intervention group and control group were comparable except the serum cortisol level (p<0.001) and the scores for Motherhood Constellation-Anxiety (p=0.032). The results showed that BRM intervention reduced the Present Behavioural Intensity and Visual Analog Scale pain scores during and after contraction (p<0.001) compared to those in the control groups, and the pain scores gradually decreased in the intervention group, while the control group did not show significant changes in their pain scores. Additionally, the level of Birth Process-Anxiety was also significantly (p<0.001) reduced in the intervention group as compared to the control group. It was observed that the level of Motherhood Constellation- Anxiety gradually increased in both the intervention and the control groups. However, the intervention group exhibited lower maternal stress hormone levels, lower maternal pulse rate and blood pressure, shorter duration of labour, and higher maternal satisfaction and APGAR scores in their newborns compared to the control group. Conclusion: The findings of this study indicate substantial effectiveness of the combined BRM interventions in relieving labour pain and anxiety, and in improving maternal and new-born outcomes among the primigravidae. It is recommended that healthcare providers involved in the childbirth of primigravidae should consider implementing this combined non-pharmacological measure to improve labour experience, maternal, and new-born outcomes.